Perspectives on Sino-Japanese diplomatic relations - Rossman, John (Japan library (Shuppan Bunka Sangyō Shinkō Zaidan), 2017)
"In East Asia, the growth center of the post-Cold War world, two regional powerhouses survey one another from opposite sides of the Japan Sea. China, a rising power with tremendous economic clout and an increasingly assertive foreign and military policy, and Japan, a respected leader in the region and a mature nation enjoying its greatest political stability in many years, must coexist for the peace and prosperity of East Asia and the Asia-Pacific. but just how well can these neighbors - and oftentimes rivals - get along? What stands in the way? And who else is caught up in their volatile relationship?"--Back cover.